Analysis Of Food Security Policy Based On Potential In The Islands Villages Of Bintan Regency - Daud, Zulkifli; Salam, Rahmat; Rudiatin, Endang; tussolekha, Izza (JIAP (Jurnal Ilmu Administrasi Publik), 2025)
This study aims to analyze food security policies in island villages and evaluate the extent to which the utilization of Village Potential and Characteristics in food security programs using village funds. This study was conducted in Bintan Regency which has many villages separated by the sea. Food security is a strategic issue in island areas because they have limited access to transportation, infrastructure and dependence on food distribution in outside areas. The objectives of the food security policy can be achieved, namely food availability, food affordability and the use of nutritious, quality and balanced food. This study aims to analyze the implementation of food security policies based on village potential, namely village funds, natural resources and human resources. The research method uses a descriptive qualitative approach with interview and observation data collection techniques. The results of the study found that the food security policy has not utilized resources according to needs, human resources, natural resources and village funds. The target of economic improvement has not been significantly felt by farmers, ranchers and fishermen so that the food security system has not been formed. It is necessary to increase the capacity of policy implementers to understand the objectives of the food security program policy based on potential.